2010
DOI: 10.1200/jco.2009.27.3367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Gene Expression–Based Classification for Neuroblastoma

Abstract: Gene expression-based classification using the 144-gene PAM predictor can contribute to improved treatment stratification of neuroblastoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 29 publications
10
94
0
1
Order By: Relevance
“…Accordingly, neither ALK mutation status nor ALK expression turned out to be independent prognostic markers in multivariate analyses considering variables of the current German risk estimation system. In light of the results of this study and others (13) as well as the high prognostic accuracy of recently published complex DNA-or RNAbased prognostic classifiers (21,26,(31)(32)(33), it remains questionable whether ALK mutation status or expression level will be useful for risk estimation of neuroblastoma patients in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, neither ALK mutation status nor ALK expression turned out to be independent prognostic markers in multivariate analyses considering variables of the current German risk estimation system. In light of the results of this study and others (13) as well as the high prognostic accuracy of recently published complex DNA-or RNAbased prognostic classifiers (21,26,(31)(32)(33), it remains questionable whether ALK mutation status or expression level will be useful for risk estimation of neuroblastoma patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the influence of genomic ALK alterations on ALK transcript levels, relative ALK mRNA expression levels were determined in all 263 tumors by using microarrays (21,26), and validated in 81 samples by qRT-PCR (Supplementary Fig. S2).…”
Section: Genomic Alk Alterations Are Associated With Elevated Alk Expmentioning
confidence: 99%
“…In our study, we corroborate this result and furthermore show by analysis of a large neuroblastoma cohort representing the whole spectrum of the disease that PLK1 expression is an independent marker of poor outcome in this malignancy. However, in light of the high prognostic accuracy of current risk-stratification strategies and complex DNA-or RNA-based prognostic classifiers (21,22,(37)(38)(39), it remains questionable, whether PLK1 expression will be utilized for risk estimation of neuroblastoma patients in the future. Western blot analysis revealed that PLK1 transcript levels correlate well with PLK1 protein levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To validate how well the cell line-based ALK downstream transcriptional profile recapitulates ALK oncogenic activity, we evaluated ALK signature scores in 2 independent gene expression datasets consisting of respectively 252 and 283 neuroblastoma tumors (19,24,25), as well as data of 2 in vivo neuroblastoma model systems (20). In human primary tumors with ALK amplification or ALK mutations, ALK signature scores were significantly higher than ALK wild-type tumors ( Fig.…”
Section: Aldh6a1mentioning
confidence: 99%